Telecommunications, Constitution and fundamental rights - Chiri Márquez, Renzo (2018)
This paper analyses the exponential development of telecommunications during these past years, and their rising impact in the exercise and enjoyment of fundamental rights. They are so necessary that the access to telecommunications in a world where globalization is constantly increasing has become a matter of great importance in order to ensure greater levels of wellbeing and development for millions of people in the planet.